Virtual Reality Applications In Malaysian's School Subject : Geography And Chemistry - Junaiza, Jarjis (2001)
This research has been emphasizing on the use of virtual reality as an education-delivering tool that is very powerful in the Malaysian's schools syllabuses context. Among the subjects that is studied its contents and VR application in them were Geography and Chemistry. Two different approaches were found to be suitable for this purposes that are Panoramic Virtual Reality and Virtual Reality Modeling Language. Among the significant thing that was found were the facilities to apply non-immersive in the primary and secondary school is less in cost compared to immersive VR. It is also found that VRML and panoramic view VR, though it is simple, they are able to help the students to increase their memory as well as their understanding.